You can't say that! : writers for young people talk about censorship, free expression, and the stories they have to tell - Marcus, Leonard S., 1950- (Candlewick Press, 2021)
Contains a collection of interviews with thirteen children's and young adult authors discussing their experiences with censorship, and examines books that have faced challenges of First Amendment Rights.